A case of multiple myeloma presenting with bullous skin lesions as the initial symptom - CHEN Lin; XU Min; GUO Qing; LUO Yijin (Pifu-xingbing zhenliaoxue zazhi)
We report a case of multiple myeloma presenting with bullous skin lesions as the initial symptom. A 62-year-old man complained of recurrent painful tense bullae and blood blisters on the buttocks and limbs for 9 months. Dermatological examination revealed tense bullae and blood blisters with mild tenderness on the limbs. Erosion and crusts were also observed. Nikolsky's sign was negative. Previous histopathology of the skin lesions revealed subepidermal bullae with negative immunoflourescence staining. Half a year ago, the patient developed pelvic and lumbar vertebral fractures. One month ago, he was diagnosed with bronchiectasis with infections, hypercalcemia, renal insufficiency, and moderate anemia at another hospital. Skin biopsy revealed subepidermal hemorrhagic bullae with a few lymphocytes in the bulla fluid and superficial dermis. Direct immunofluorescence showed negative for IgG、IgA、IgM and C3. Immunohistochemistry showed weakly positive for lambda light chain and negative for kappa light chain around the bullae. Congo red staining was negative. Further tests of serum and urine immunoelectrophoresis showed that λ light chain and free-λ light chain were positive. The bone marrow histology was consistent with a plasmacytoma. The patient was diagnosed with multiple myeloma. The patient was treated with methylprednisolone 20 mg/d, antibiotic and calcitonin. Two days later, the patient experienced an unprovoked cerebral infarction. Subsequent telephone follow-up at two weeks revealed the patient had deceased.